Implementation of Community Protection of Gurabunga Customary Law: An Empirical Analysis of Customary Law Practices and Their Recognition by the State - Siti Barora Sinay; Sultan Alwan; Irham Rosyidi (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Gurabunga Village, located in Tidore District, Tidore Islands City, has a long history as part of the Tidore Sultanate and is an area with customary law communities that still preserve their traditions. This study aims to examine the process of changing the status of Gurabunga Village to a Customary Village, as well as its implications for the recognition and legal protection for the Gurabunga customary law community. The method used is empirical legal research with a sociolegal approach, collecting data through interviews, observations, and studies of related legal documents. The results of the study show that the Gurabunga community has appropriate characteristics to be recognized as a customary law community based on Permendagri No. 52 of 2014, with customary wealth in the form of customary land that is managed communally and protected by local customary law. The process of changing this status involves community initiatives through village deliberations, fulfillment of administrative requirements, and local government approval. Meanwhile, the biggest challenge in the implementation of legal protection of customary rights is the lack of understanding from local governments regarding the importance of recognizing the rights of customary law communities. Therefore, this study suggests the importance of strengthening regulations and empowering customary law communities through more inclusive policies. The recommendation of this study is to accelerate the recognition of indigenous peoples in Indonesia, by providing space for communities to fight for their indigenous rights within a national legal framework that is responsive and adaptive to local social and cultural needs